How Radical Environmental Sabotage Impacts US Elections - Farrer, Benjamin (Terrorism and political violence, 2022)
In this paper we examine the impact of forceful or violent environmental sabotage (FVES) on U.S. elections. We argue that voters see ideological similarities between groups that engage in FVES and other nonviolent environmental organizations, like the Green Party. This means that when an environmentalist organization engages in FVES, it has a negative impact on voter attitudes toward all environmental organizations. Moreover, this negative impact will be stronger if environmentalists had previously made electoral progress, and so they cannot use the excuse that democratic methods had failed and they were forced to turn to FVES. We demonstrate this by showing that when FVES occurs, Green Party candidates tend to win a lower share of the vote in the next election. However, this effect is conditional on the prior electoral history of the Green Party. If the Green Party has a poor electoral record, then sabotage has little effect, but if the Green Party has a better electoral record, then voters are less forgiving of sabotage. We find no evidence that FVES effects Republican or Democratic vote shares. We conclude that different organizations within the same social movement are connected in ways that impact electoral outcomes.